Characterization and modulation of CCR6/CCL20-mediated immunosurveillance in malignant melanoma - Martín-García, Diego (2019)
Abstract: Chemokine ligand 20 (CCL20) expressed in the epidermis is a potent impetus for the recruitment of subsets of DCs, B-cells and memory T-cells expressing its exclusive receptor chemokine receptor 6 (CCR6) into the skin. CCL20 and a corresponding CCR6-expressing immune cell infiltrate have been detected in chronic inflammatory skin diseases and several malignancies, including melanoma. Yet, the functional contribution of the CCR6/CCL20 axis for the immune control of melanoma remains controversial. The characterization of CCR6-guided immune cell subsets and their functional contribution for the immune control of melanoma comprises the main focus of this project. We evaluated the homeostatic and inducible secretion of CCL20 by different murine and human melanoma cell lines by ELISA. Both murine (B16, Ret) and human (A375, C32) melanoma cell lines are capable of up-regulating CCL20 secretion upon stimulation with pro-inflammatory cytokines in vitro . In order to determine the functional relevance of CCR6 on local tumor growth, B16/F1 melanoma cells retrovirally transduced with a vector that constantly overexpresses CCL20 (B16-CCL20) were injected subcutaneously in C57BL/6 wt mice and congenic CCR6-knockout (CCR6-/-) mice. While animals in both groups developed local tumors, we observed a significantly reduced tumor growth in CCR6-/- mice. By contrast, Wt and CCR6-/- control groups did not display differences in tumor growth rate. Our results suggest that CCL20 interactions in the microenvironment of cutaneous melanoma may be an essential factor for local tumor growth, although the precise mechanisms require further investigation.
Keywords: Hochschulschrift